Penerapan Model Project Based Learning (PjBL) dalam Meningkatkan Critical Thinking Peserta Didik pada Pelajaran IPAS - Ragil Sunita; Sati Sati; Nurkholis Nurkholis (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research is motivated by the low level of critical thinking skills of class V. this can be evidenced by the results of observations and interviews conducted with class v teachers, which show that student are quite responsive in answering questions, but they are not yet able to answer questions that require explanation. Out of the 12 students, only 4 students are actively asking questions during learning. This is because the learning model used is less effective and does not motivate students. This research aims to enhance students critical thinking skills by implementing the Project Based Learning (PjBL) model. This research employs a Classroom Action Research (CAR) methodology. The research design is based on the Kemmis and Taggart model, which encompasses four stages: planning, implementation, observation, and reflection. The research findings indicate a significant improvement in students critical thinking skills, with a 50% increase in cycle I and an 83,33% increase in cycle II following the implementation of the Project Based Learning (PjBL) model.